Local Warming, Local Economic Growth, and Local Change in Democratic Culture - Van de Vliert, Evert; TOL, RICHARD S. J. (ESRI, 2011)
In a 104-nation study we first demonstrate that cultural self-expression, individualism and democracy languish in poor countries with colder-than-temperate winters, but flourish in rich countries with such winters. Mild summers are kind to this syndrome of culturally embedded democracy in rich countries only. Using these climato-economic niches of culture, we then estimate how unarrested global warming in conjunction with unaltered economic growth would affect democratic culture in 138 countries and regions. Local warming in concert with local economic trends would weaken democratic culture, especially the strongly democratic cultures of Australia, New Zealand, Northern Europe, and North America, but would strengthen democratic culture in China and Russia.
PUBLISHED
Keywords: growth; North America; europe